PIDANA MATI DALAM PERSPEKTIF HUKUM PIDANA DAN HUKUM PIDANA ISLAM - Roni Efendi (JURIS (Jurnal Ilmiah Syariah), 2017)
Debatable of the death penalty actually based on the issue of justice, humanity and the prevention of the possibility of crime. The reasons for the rejection of the death penalty are not justified in the view of life as well as humanitarian factors and the imposition of capital punishment will not be able to prevent crime and reduce crime rates. But for those who agree with the imposition of capital punishment because of the sense of justice and peace that is in the community. The portrait is just a glimpse of the issue that colored the discourse on the pros and cons of the existence of capital punishment. Between the retensionist and the abilitionist against true the death penalty has an argument each based on his theoretical framework and norms. Indonesia as one of the countries with the European Continental legal system still apply the death penalty in punishment system beside Saudi Arabia with qhisash which  applid in Islamic Law system. Both countries have a legal standing built on the meta norms, their theories and philosophies each of course has its own urgency to be discussed in the midst of countries that condemn the existence of capital punishment. Here's an article that analyzes comparative relation to the application of thedeath penaltyin both countries that embraces the different legal system, from this comparative study will contribute thoughts in the reform of criminal law in Indonesia.